2020
DOI: 10.7150/ijbs.39769
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive understanding of B7 family in gastric cancer: expression profile, association with clinicopathological parameters and downstream targets

Abstract: Objectives: B7 family members were identified as co-stimulators or co-inhibitors of the immune response and played important roles in cancer immunotherapy; however, their dysregulation in gastric cancer is still unclear. Methods: Data were obtained from TCGA and GTEX database. B7 mutations, association with DNA methylation and affected proteins were analyzed in cBioportal. Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis and Gene Ontology (GO) project was studied by DAVID to find the downstre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 37 publications
2
35
0
Order By: Relevance
“…Different research groups showed that B7‐H6 has no significant diagnostic or prognostic value in non‐small cell lung cancer and gastric cancer (26, 27). With the data from TCGA and GTEX database, Li and his colleagues revealed that the high expression of B7‐H6 was associated with good overall patient survival in gastric cancer (25). Cao et al recently showed that expression of B7‐H6 in chronic myeloid leukemia (CML) was negatively correlated with the copy number of fusion gene BCR‐ABL1, and furthermore, the patients with high B7‐H6 level had significantly longer progression‐free survival than those with low B7‐H6 expression level (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different research groups showed that B7‐H6 has no significant diagnostic or prognostic value in non‐small cell lung cancer and gastric cancer (26, 27). With the data from TCGA and GTEX database, Li and his colleagues revealed that the high expression of B7‐H6 was associated with good overall patient survival in gastric cancer (25). Cao et al recently showed that expression of B7‐H6 in chronic myeloid leukemia (CML) was negatively correlated with the copy number of fusion gene BCR‐ABL1, and furthermore, the patients with high B7‐H6 level had significantly longer progression‐free survival than those with low B7‐H6 expression level (28).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that the expression of B7‐H6 is related to the metastasis of some cancers, and the B7‐H6 expression is negatively correlated with the overall survival (OS) rate of ovarian cancer, breast cancer, brain tumor, esophageal squamous cell carcinoma, cervical cancer, and esophageal squamous cell carcinoma (17, 19–24). However, the situation is not always the same, and it was found that the higher expression of B7‐H6 predicted favorable overall patient survival in gastric cancer (25). Moreover, the clinical significance of B7‐H6 in HCC patients remains uncertain.…”
mentioning
confidence: 99%
“…Different B7 molecules have either positive or negative co-stimulatory signals while modulating immune cell responses (Table 1) [4,5]. Immune checkpoints, such as PD-1, PD-L1, PD-L2, and CTLA4, are molecules holding many receptor-ligand interactions to evade the immune system and facilitate proliferation.…”
Section: B7 Familymentioning
confidence: 99%
“…Differential proteins are shown by the volcano plot using GraphPad Prism 7. The selected proteins from this criterion were used to predict pathways by two conditions: (a) the sum of altered protein in each pathway and (b) the statistical P value score of significant pathway ( Li D. et al, 2020 ). Finally, the screened differential proteins were used to predict the pathway in the DAVID function annotation tool 4 .…”
Section: Methodsmentioning
confidence: 99%